Evaluation of universities service quality through Servqual method - Anisseh Mohammad; Sharifi Narges; Akbari Zahra (Journal of Engineering Management and Competitiveness, 2023)
Universities play a crucial role in societal development and growth, with higher education expanding every day. Therefore, it is essential for universities to prioritize the quality of educational services to ensure student satisfaction. Evaluating the quality of educational services is a fundamental step in improving higher education. This research is an applied study that uses descriptive and exploratory methods for data collection. The statistical population for this research includes students from the Faculty of Social Sciences at Imam Khomeini International University and the Faculty of Management at Tehran University. To gather information, a standard Servqual questionnaire was used to measure the significance of each educational service criterion on student satisfaction levels. In the end, the results have been reviewed and analyzed.